PENGEMBANGAN MEDIA PEMBELAJARAN ULTRA (ULAR TANGGA INTERAKTIF IPAS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Lamada, Herawati; Abdullah, Gamar; Arif, Rifda Mardian; Panai, Abdul Haris; Arifin, Vicka Muniati (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this study was to develop ULTRA (Interactive Snakes and Ladders of Science) learning media that meets the criteria of feasibility, practicality, and effectiveness in science learning to improve student learning outcomes in ecosystem material in grade V of SDN 1 Suwawa. This study is a development research using the ADDIE development research model, which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility of ULTRA media was tested through validation by a team of experts. The validation results showed that this media obtained an average percentage of 96.87%, which was categorized as very feasible for use by teachers and students in elementary schools. To test practicality, the researcher used a teacher observation sheet, which showed a total score of 39 out of a maximum score of 40, with an average percentage of practicality reaching 97.5%, included in the very practical category. In terms of effectiveness, the application of media in grade V of SDN 1 Suwawa was measured through pretest and posttest. As a result, the average pretest score of 46.5% increased to 86% in the posttest, with a difference in increase of 39.5%. The level of effectiveness of ULTRA media based on calculations reached 73.55%, indicating that ULTRA media is included in the effective category. Based on these results, ULTRA media has proven effective in improving student learning outcomes and is suitable for use in elementary school learning